Electrolyte abnormalities and type of feeding in acute diarrhoea in children upto five years - S. , Prakash; S., Saravanan (International Journal of Contemporary Pediatrics, 2023)
Background: Children in infancy are protected against diarrhoea by breastfeeding as suggested by many studies. Failure to exclusively breastfeed and early introduction of complementary feeds in children predispose to several diseases especially diarrhoea. This study was mainly aimed at analysing electrolyte abnormalities in children with diarrhoea in relation to their type of feeding. Methods: Around 100 children under five years of age with acute diarrhoea presenting to paediatrics department were enrolled in the study after meeting the inclusion criteria. The electrolyte abnormalities, glucose level, renal parameters, severity of dehydration and type of feeding of the children were recorded. The incidence of electrolyte abnormalities in diarrhoea in the children and their type of feeding were analysed. Results: Participants had hyperkalaemia which was 30%, followed by 19% had hyponatremia, 13% had hypokalaemia, 12% had hypernatremia and 1% had hyperchloremia. 38% had no dehydration, 8% had severe dehydration and 54% had some dehydration. 49% of the children followed breast feeding, 16% followed formula feeding, 14% were taken cow’s milk and 21% were followed mixed feeding. There was no statistically significant relationship between electrolyte abnormalities and type of feeding except for hypokalemia. Conclusions: Except with hypokalaemia, our study did not find a statistically significant relationship between electrolyte abnormalities in diarrhoea in children with type of feeding. But still, need for exclusive breastfeeding, continuation breast feeding more than two years remains protective against acute diarrhoea in children.